Occupational Safety and Health Education Experience and Prevention Service Needs among South Korean Farmers: A National Survey. Issue 1 (2nd January 2022) - Kim, Kyungsu; Kim, Hyocher; Choi, Dongphil; Lee, Hyeongyeong; Kim, Insoo; Choi, Wonjong
ABSTRACT: Objective: Objective data on farmers' awareness of occupational safety and health are needed for the development of national policy measures. Yet, relevant research is lacking in South Korea. Methods: This study investigated occupational safety and health education experience, perceived needs for prevention services, and factors affecting these among South Korean farmers. The data are from a personal-visit survey conducted on 9, 970 sample farms nationwide. Results: While 69.9% of the farmers felt the need for agricultural health and safety education and 60.6% were willing to receive it, only 30.3% had at least one educational experience. A total of 51.9% felt the need for professional on-farm services. By group, education experience and perceived need for prevention services were consistently low among women, people aged 70 or older, low-income individuals, or farmers with a farming career duration of less than five years. Experience of safety and health education increased the desire for other prevention services: people who had received safety and health education were 6.4 times more likely to feel the need for education, 5.5 times more willing to participate in education, 2.0 times more likely to feel the need to improve their work environments, and 1.7 times more likely to feel the need for professional on-farm services. Conclusion: Despite the high desire for injury prevention services, farmers have had very limited opportunities to receive safety education; measures are also needed for groups whose safety education has been neglected. Further studies on education methods and on-farm services tailored to South Korean farmers are needed.